Peningkatan sikap rasa ingin tahu peserta didik dalam pembelajaran IPA menggunakan model problem based learning (PBL) - Resa Nugroho Jati; Idam Ragil Widianto Atmojo; Sularmi Sularmi (Didaktika Dwija Indria, 2020)
Abstract. This study aims to improve students' curiosity attitudes by applying the Problem based learning learning model. This research is a class action research with three cycles. The subject of this study was 36 grade elementary school students in the academic year 2019/2020, totaling 36 students. Data collection techniques use the results of observations, interviews and documentation. Data validation using the Triangulation technique. The data analysis model used is Miles and Huberman's interactive analysis model with 4 components. The results of the study show that the application of the problem based learning model can raise the curiosity attitude of fifth grade elementary school students in the academic year 2019/2020. Keywords: curiosity attitude, problem based learning model, elementary school